The importance of urinary calcium in postmenopausal women with osteoporotic fracture - Ochoa-Hortal Rull, Miguel Angel; Cano-Garcia, Maria del Carmen; Arrabal Martin, Miguel; Arrabal-Polo, Miguel Angel (Canadian Urological Association Journal, 2015)
Introduction: Calcium stones are associated with osteoporosis and manifested mainly by elevated fasting urinary calcium/creatinine ratio. The objective of this study is to demonstrate the presence of abnormal metabolism of calcium and calciuria in women with osteoporotic fracture with no previously known renal lithiasis compared to women without osteoporosis and without renal lithiasis. Methods: In total, 87 women were included in the study. They were divided into two groups: Group 1 with 55 postmenopausal women with osteoporotic fracture and without renal lithiasis; and Group 2 with 32 postmenopausal women without osteoporosis and without history of renal lithiasis. The following parameters of phospho-calcium metabolism were analyzed: calciuria 24-hour, oxaluria 24-hour, uricosuria 24-hour, and citraturia 24-hour. The presence of hypercalciuria, hyperoxaluria, hyperuricosuria, and hypocitraturia was compared between groups. Statistical significance was set at p ≤ 0.05. Results: The mean age was 70.1 ± 13.8 in Group 1 and 56.7 ± 6.4 in Group 2 (p = 0.0001). Women in Group 1 had higher levels of serum alkaline phosphatase (p < 0.05) and fasting urinary calcium/ creatinine ratio (p < 0.05). The percentage of patients with hypercalciuria in Group 1 (40%) was higher compared to Group 2 (18.8%) and statistically significant (p = 0.04). There were no statistically significant differences in the percentage of hyperoxaluria, hyperuricosuria, and hypocitraturia between groups. This study has its limitations including its cross-sectional nature at a unique centre and its low number of patients. Conclusion: The determination of urinary calcium and fasting calcium/ creatinine ratio in postmenopausal women with osteoporotic fracture without renal lithiasis may facilitate individualization of medical therapy and decreasing lithogenic risk.